TPR (TOTAL PHYSICAL RESPONSE) METHOD ON TEACHING ENGLISH TO EARLY CHILDHOOD - Ruli Hafidah; Nurul Kusuma Dewi (Early Childhood Education and Development Journal, 2020)
This training is carried out to provide knowledge and skills to PAUD teachers in implementing English language learning for early childhood. The subjects of the training were 30 Kindergarten (Kindergarten) and PAUD teachers of Bendosari kindergarten. The training is carried out in 3 stages, namely: (1) strengthening of materials related to the TPR (Total Physical Response) method in early childhood learning; (2) implementation of the TPR (Total Physical Response) method in learning aged children; and (3) evaluation of the material for the TPR (Total Physical Response) method in learning children. Training on the application of the TPR (Total Physical Response) method in learning English for early childhood can improve the understanding, abilities and skills of Kindergarten and PAUD teachers in the District, Sukoharjo Regency in compiling, developing, and implementing English learning using the TPR (Total Physical Response) method. Where the deepening of the material for each training stage reaches 90%. This is evidenced by the results of practice and the implications of each material. Kindergarten and PAUD teachers in Bendosari Subdistrict, Sukoharjo Regency can develop themes and materials, create and use media, choose English vocabulary according to themes and materials, and apply English learning using the TPR (Total Physical Response) method.